Cultural theory and popular culture a reader - Storey, John 1950- (Routledge, 2019)
"The fifth edition of John Storey's successful Cultural Theory and Popular Culture Reader is an essential companion volume to Cultural Theory and Popular Culture: An Introduction, now in its eighth edition. The reader offers students the opportunity to experience first-hand the theorists and critics discussed in Cultural Theory and Popular Culture: An Introduction through crucial articles and essays spanning over a hundred years of cultural theory. It can be used both in conjunction with and independently of the textbook. Taken as a whole, this book provides a theoretical, analytical and historical introduction to the study of popular culture and provides key primary coverage of fundamental issues in cultural studies. This edition includes: - a new section on Class, as well as additional readings on Sexuality and Gender. - fully revised general and section introductions from the editor, contextualising and linking the readings with key issues from the textbook - fully updated bibliography The new edition is essential reading for undergraduate and postgraduate students of cultural studies, media studies, communication studies, the sociology of culture, popular culture and other related subjects"--